Characterization of α-Fe2O3 nanorod arrays prepared by a quasi-topotactic transformation of solvothermal derived β-FeOOH nanowire-like arrays. (December 2020) - Taniguchi, K.; Kitazawa, N.
Abstract: Vertically aligned α-Fe2 O3 nanorod arrays were synthesized by a quasi-topotactic transition of solvothermal derived β-FeOOH nanowire-like arrays on a fluorine-doped tin oxide (FTO) coated glass substrates. Co-existence of chloride ions and acetonitrile in the precursor solutions was found to be essential for synthesizing [211]-oriented β-FeOOH nanowire-like arrays. Field-emission scanning electron microscopy (FE-SEM) observation revealed that heterogeneous nucleation of β-FeOOH preferentially occurs on ridges of the FTO crystal than flat surfaces. High-resolution transmission electron microscopy (HR-TEM) and selected-area electron diffraction (SAED) studies revealed that the [110]-oriented α-Fe2 O3 nanorod arrays were successfully formed. [110]-oriented α-Fe2 O3 nanorod arrays prepared by this method exhibit pronounced photocurrent response under visible light illumination. Photo-electrochemical properties of α-Fe2 O3 nanorod arrays were discussed from the viewpoint of its electronic and crystal structures. Highlights: Hematite nanorod arrays have been synthesized by a quasi-topotactic transition. Direct evidence of quasi-topotactic transition was confirmed by HR-TEM and SAED. [110]-oriented hematite nanorod arrays showed photoelectrochemical water oxidation.